CHROMOLAENA ODORATA BLESSING OR CURSE? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
CHROMOLAENA ODORATA BLESSING OR CURSE?In Cameroon, women complain bitterly that since Chromolaena odorata appeared in their fields they have to spend twice as long weeding as before. It is absolutely essential that this weed is dug out completely....